(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Teaching a foreign language involves not only linguistic competence but also cultural awareness. This study explores the integration of linguistic and cultural elements in language instruction. It examines effective teaching strategies that foster both language proficiency and cultural understanding. Findings suggest that a balanced approach incorporating linguistic theory, practical communication, and cultural immersion enhances language acquisition.